Proceedings of the multi-actor and multi-disciplinary trainings and consultations on food waste prevention and reduction in Sri Lanka - Aheeyar, Mohamed M. M.; Jayathilake, Nilanthi; Drechsel, Pay; Bucatariu, C. (FAO; IWMI, 2023)
Sustainable Development Goal (SDG) 12.3 of the UN 2030 Agenda calls for halving per capita global food waste (FW) from retail to households. Food waste (FW) prevention and reduction play a major role in ensuring the sustainability of food systems as well as effective Solid Waste Management (SWM). A coherent, coordinated, and complementary approach to quantification causes identification, and scaling up feasible solutions is necessary. Awareness-raising and capacity development for food supply chain actors, the public sector, and civil society organizations is required for successful interventions. The Project Innovative approaches to reduce, recycle and reuse FW in urban Sri Lanka was implemented under the oversight of the Ministry of Urban Development, and Housing in collaboration with the Food and Agriculture Organization of the United Nations (FAO) and the International Water Management Institute (IWMI) from June 2019 to August 2021. The project produced a series of reports and papers including FAO and IWMI (2021a), FAO and IWMI (2021b), FAO and IWMI (2021c), and FAO and IWMI (2021d) that were used in the awareness creation and capacity development programmes. The major output of the Project was to facilitate knowledge development for and drafting of the Urban Roadmap on FW Prevention, Reduction, Management in Sri Lanka, that includes a comprehensive Action Plan with Monitoring and Evaluation criteria. The objective of this report is to summarize the proceedings of the consultations and sensitization sessions conducted from June 2019 to June 2021.